2002
DOI: 10.1080/08880010252899451
|View full text |Cite
|
Sign up to set email alerts
|

CENTRAL PRECOCIOUS PUBERTY IN MULTISYSTEM LANGERHANS CELL HISTIOCYTOSIS: A Case Report

Abstract: The authors describe a girl with multisystem Langerhans cell histiocytosis (LCH) who developed central precocious puberty (CPP). At the age of 19 months she presented with otorrhea and polypoid formations in the ear canal; polyps were removed and LCH suspected. She subsequently developed diabetes insipidus with a documented lesion of the pituitary stalk; she received chemotherapy and began therapy with l-desamino-8-D-argininevasopressin. Growth hormone deficiency was diagnosed at the age of 4.4 years and GH re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Nanduri et al [33] reported 1 boy with LCH who had an early onset of puberty requiring treatment with a gonadotropin-releasing hormone analogue for a period of 20 months. Another reported case was a 7.5-year-old girl with multisystem LCH, CDI, GH deficiency, and central hypothyroidism who developed central precocious puberty [66]. Finally, Table 1 describes the frequency of pituitary involvement in the latest paediatric series.…”
Section: Lch: Hypothalamus-pituitary Involvementmentioning
confidence: 99%
“…Nanduri et al [33] reported 1 boy with LCH who had an early onset of puberty requiring treatment with a gonadotropin-releasing hormone analogue for a period of 20 months. Another reported case was a 7.5-year-old girl with multisystem LCH, CDI, GH deficiency, and central hypothyroidism who developed central precocious puberty [66]. Finally, Table 1 describes the frequency of pituitary involvement in the latest paediatric series.…”
Section: Lch: Hypothalamus-pituitary Involvementmentioning
confidence: 99%
“…The French LCH study group describes gonadotropin deficiency in 12% of children with DI whereas Maghnie et al did not see any abnormal gonadotropin status in the 17 LCH children (11 with multisystem disease) despite one-third being pubertal or postpubertal [1,6]. A single report in the existing English literature describes central precocious puberty in a 7.5-yr-old LCH girl, 6 years after disease onset [7]. The present patient presented with precocious puberty at 5.5 yrs age, 2 years after disease onset.…”
Section: Discussionmentioning
confidence: 90%
“…While the risk for evolving anterior pituitary hormone deficiencies is ongoing and international guidelines suggest regular growth and pubertal follow-up, there are very limited data on incidence of atypical puberty in LCH. [13][14][15] Bisphosphonate use in LCH has been documented since 1989, to treat bone pain, in addition to improvement of bone mineral density. 16 In this cohort three were noted to have multiple fractures in the setting of LCH.…”
Section: Discussionmentioning
confidence: 99%